The g-good-neighbour conditional diagnosability of enhanced hypercube under PMC model. Issue 1 (2nd January 2020) - Yu, Hui; Huang, Yanze; Lin, Limei; Li, Jin'e; Chen, Riqing
Abstract : The significant increase in the number of processors of multiprocessor system increases its vulnerability to component failures. Diagnosability is an important indicator for the reliability of interconnection networks. The g -good-neighbour conditional diagnosability is the maximum number of faulty vertices a network can guarantee to identify, under the condition that every fault-free vertex has at least g fault-free neighbours (i.e. good neighbours). In this paper, we establish that the 1-good-neighbour conditional diagnosability of ( n, k ) -enhanced hypercube network Q n, k under PMC model is 2 n −1 for n = k + 1 and k ≥ 3, or 2 n + 1 for n > k + 1 and k ≥ 3, respectively. Moreover, the 2-good-neighbour conditional diagnosability of Q n, k is 3 n −3 for n = k + 1 and k ≥ 4, or 4 n −5 for n = k + 2 and k ≥ 3, or 4 n −1 for n > k + 2 and k ≥ 3, respectively.